Implementation of the Child Protection Act: Evaluation and Recommendations - Tasya, Tasya (PT. Hafasy Dwi Nawasena, 2025)
The implementation of the Child Protection Law in Indonesia is an important step to guarantee children's rights and provide protection from various forms of violence and exploitation. Although there is a supporting legal framework, challenges in its implementation often hinder the effectiveness of this law. This study aims to evaluate the implementation of the law, identify influencing factors, and provide recommendations for improving policies and practices in the field. Through the Systematic Literature Review (SLR) approach, this study collects and analyzes various relevant literature on the implementation of the Child Protection Law. The results of this study indicate a gap between formulated policies and practices in the field, and provide insight into the steps that need to be taken to improve the effectiveness of child protection in Indonesia. With these findings, it is hoped that it can be a reference for policy makers, legal practitioners, and the community in strengthening child protection in Indonesia